2017
DOI: 10.5004/dwt.2017.21279
|View full text |Cite
|
Sign up to set email alerts
|

Improving the yield of fresh water from conventional and stepped solar still with different nanofluids

Abstract: a b s t r a c tThis experimental work intensively studies the effect of nanoparticle concentration on conventional and stepped solar still. An experimental study was conducted with concentration ranging from 0.05 to 0.2% with Al 2 O 3 , CuO and TiO 2 both on conventional and stepped solar still. Results showed that by incorporating nanoparticles in the base fluid improves the yield of fresh water from conventional and stepped solar still by 50 and 67% respectively while using Al 2 O 3 nano fluid. The temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…ZJPS heat ow is composed of several components and temperature components. Using Laplace transform, this study discovered time-variable values for rst-order differential equations in ordinary differential equations from ( 15) to (19). Equations ( 20) to (24) were employed as the answer to get to the double approaches for the DUSD's elements (temperatures) using ZJP performance.…”
Section: (C)mentioning
confidence: 99%
See 1 more Smart Citation
“…ZJPS heat ow is composed of several components and temperature components. Using Laplace transform, this study discovered time-variable values for rst-order differential equations in ordinary differential equations from ( 15) to (19). Equations ( 20) to (24) were employed as the answer to get to the double approaches for the DUSD's elements (temperatures) using ZJP performance.…”
Section: (C)mentioning
confidence: 99%
“…The overall energy and exergy e cacies of the nano uids DSSD study were 37.78% and 4.92%, respectively. (Madhu et al 2017) studied the stepwise solar distillers produced by Al 2 O 3 , TiO 2 , and CuO nano uids. (Kabeel et al 2017) produced the black paint with Cu 2 O 4 combined and coated on the absorber plate distiller, resulting in higher freshwater gathering in the distiller.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed method is fundamentally different from all current methods of water production. This method does not require transporting fresh water over long distances, it is inexpensive and environmentally friendly [6], [7]. Atmospheric air contains about 14,000 cubic kilometers of water in the form of steam [8], [9], [10], [11] and thus it can be used as a new and renewable water source.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, from the exegetic analysis, it has been found that the increment of 11.12% in the case of Al 2 O 3 nanoparticle has the volume concentration of φ = 0.2%. Madhu et al investigated the effect of concentration of Al 2 O 3 , CuO, and TiO 2 nanoparticles in fluid for improving the performance of stepped solar still. Results indicated the increment of distillate output of 50% and 67% for conventional as well as stepped one using higher thermal conductivity nanoparticle with the fluid (Al 2 O 3 ).…”
Section: Introductionmentioning
confidence: 99%